Kampung Ramah Anak: Upaya Penerapan Program Perlindungan dan Pemenuhan Hak Anak Di Kampung Karanganyar Kelurahan Brontokusuman Kemantren Mergangsan Kota Yogyakarta - Apriliyani Apriliyani; Suwarjo Suwarjo (Universitas Widya Mataram, 2026)
Since implementing the Child-Friendly City (KLA) program in 2009, Yogyakarta City has successfully obtained the Nindya predicate in 2018-2019, one of which is through the Child-Friendly Village (KRA) Program strategy. However, over time, the implementation of the KRA Program is not without problems. One of the problems is the high population dynamics and mobility and the density of personal activities which are one of the causes of several KRA Villages experiencing stagnation in their activities. This study aims to describe the implementation of the KRA Program in the Child-Friendly Village of RW 16, Karanganyar Brontokusuman Mergangsan Village, Yogyakarta City. This study uses a qualitative approach with informants from the KRA Task Force administrators and several related agencies. Triangulation techniques are used to test the validity of the data obtained before being presented. The results of the study indicate that the implementation of the KRA Program in Karanganyar Village RW 16 in 5 (five) clusters has not been running well. The implementation model from Edwards III shows the existence of communication factors, resources, implementer attitudes, and bureaucratic structures that are less than optimal in supporting program implementation. The decline in communication and coordination between administrators since 2020 due to their busy schedules is one of the contributing factors. Furthermore, limited program funding sources also hamper the implementation of the KRA program. Government funding remains severely limited. Government assistance is provided primarily in the form of counseling and mentoring. To support funding, efforts have been made to raise funds from community contributions, but the amounts are relatively small. The business sector has also provided assistance in the form of goods or facilities. Keywords: Program Implementation; Child-Friendly Villages; Child Protection.